2016
DOI: 10.1097/qad.0000000000001021
|View full text |Cite
|
Sign up to set email alerts
|

Short message service (SMS) reminders and real-time adherence monitoring improve antiretroviral therapy adherence in rural Uganda

Abstract: Objective:To explore the effects of four types of short message service (SMS) plus real-time adherence monitoring on antiretroviral therapy (ART) adherence: daily reminders, weekly reminders, reminders triggered after a late or missed dose (delivered to patients), and notifications triggered by sustained adherence lapses (delivered to patient-nominated social supporters).Design:Pilot randomized controlled trial.Methods:Sixty-three individuals initiating ART received a real-time adherence monitor and were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
156
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 17 publications
14
156
1
Order By: Relevance
“…Some of this bias can be reduced in analyzing the adherence data (e.g., censoring more openings than would be expected per day). Additionally, complementing adherence monitoring with assessment of biological indicators (such as viral loads) as done in this study [14] can improve the interpretation of adherence reports generated by using the monitor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of this bias can be reduced in analyzing the adherence data (e.g., censoring more openings than would be expected per day). Additionally, complementing adherence monitoring with assessment of biological indicators (such as viral loads) as done in this study [14] can improve the interpretation of adherence reports generated by using the monitor.…”
Section: Discussionmentioning
confidence: 99%
“…Complete study details are published elsewhere [14]. Briefly, a total of 63 study participants were enrolled and followed for nine months.…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The concurrent emergence of low-cost, easy-to-use mobile health (mHealth) applications like telephone-based short-messaging services (SMS) and chat applications like WhatsApp have facilitated a variety of new interventions to enhance communication between patients and health-care providers. While communicating health information via mobile phones seems to be acceptable [3][4][5], mHealth studies have reported varying levels of success at improving patient wellbeing and clinical outcomes [6][7][8][9][10][11][12][13]. Potential explanations for this variability may arise from a failure to plan for, collect, or report key process measures important for characterizing the implementation of mHealth interventions.…”
Section: Introductionmentioning
confidence: 99%